Comment on "Relict Basin Closure and Crustal Shortening Budgets During Continental Collision: An Example From Caucasus Sediment Provenance" by Cowgill et al. (2016). Issue 3 (25th March 2018) - Vincent, Stephen J.; Saintot, Aline; Mosar, Jon; Okay, Aral I.; Nikishin, Anatoly M.
Plain Language Summary: The southern slope of the Greater Caucasus mountains is the site of a former rift basin. In order to explain shortening deficits, plate deceleration, and the ~5 Ma reorganization of the Arabia‐Eurasia collision zone Cowgill et al. (2016) proposed that this basin closed ~5 Myrs ago. Within the western Greater Caucasus, at least, careful examination of sedimentological, provenance, and seismic data, however, supports an earlier ~35 Ma basin closure age. Basin closure cannot therefore be the driving mechanism for the ~5 Ma deceleration of the Arabian plate and reorganization of the Arabia‐Eurasia collision zone. Key Points: Cowgill et al.'s model for Greater Caucasus Basin closure at 5 Ma is not supported by any sedimentological, provenance, or structural data Oligo‐Miocene samples were instead deposited in the southern foreland of the Greater Caucasus following basin closure at ~35 Ma Their sparse Jurassic to Eocene provenance data set is insufficient to provide any meaningful insights into the former width of the basin